2017
DOI: 10.4103/ija.ija_581_17
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of oral tolvaptan versus 3% hypertonic saline for correction of hyponatraemia in post-operative patients

Abstract: Background and Aims:Hyponatraemia is frequent in post-operative patients and may be corrected with hypertonic saline (HTS). Oral tolvaptan is used to treat hypervolaemic or euvolaemic hyponatraemia. This study was performed to assess the efficacy of oral tolvaptan in correcting postoperative hyponatraemia compared to HTS.Methods:This prospective, randomised study was conducted in 40 symptomatic patients with serum sodium level ≤130 mEq/L. In Group H (n = 20), 3% HTS was infused at 20–30 mL/h aiming for correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Vaptans are arginine-vasopressin receptor antagonists whose efficacy and safety has been demonstrated in randomized clinical trials for the treatment of hypervolemic and euvolemic hyponatremia ( 16 , 17 ). The use of these medications in the post-operative setting ( 18 , 19 ) and in critical neurological and neurosurgical adult patients ( 20 , 21 ) has shown that vaptans allow correction of hyponatremia with the rare occurrence of adverse effects.…”
Section: Introductionmentioning
confidence: 99%
“…Vaptans are arginine-vasopressin receptor antagonists whose efficacy and safety has been demonstrated in randomized clinical trials for the treatment of hypervolemic and euvolemic hyponatremia ( 16 , 17 ). The use of these medications in the post-operative setting ( 18 , 19 ) and in critical neurological and neurosurgical adult patients ( 20 , 21 ) has shown that vaptans allow correction of hyponatremia with the rare occurrence of adverse effects.…”
Section: Introductionmentioning
confidence: 99%